2013
DOI: 10.1088/0963-0252/22/6/065011
|View full text |Cite
|
Sign up to set email alerts
|

Electron densities and energies of a guided argon streamer in argon and air environments

Abstract: In this study we report the temporally and spatially resolved electron densities and mean energies of a guided argon streamer in ambient argon and air obtained by Thomson laser scattering. The plasma is driven by a positive monopolar 3.5 kV pulse, with a pulse width of 500 ns and a frequency of 5 kHz which is synchronized with the high repetition rate laser system. This configuration enables us to use the spatial and temporal stability of the guided streamer to accumulate a multitude of laser/plasma shots by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
48
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 38 publications
12
48
0
Order By: Relevance
“…The detection limits are mostly determined by the laser stray light and are in the order n e > 10 12 cm -3 . 52 The electron densities estimated in this work are well below 10 12 cm À3 just before the exit of the tube. In order to make better comparison with the measurements of the electron density by Thomson scattering and the estimation presented in this article, we calculated electron densities in the tube and the effluent of the plasma jet operating with gas flow of 1000 SCCM.…”
Section: Estimations Of the Electron Density In The Streamer Channelmentioning
confidence: 59%
“…The detection limits are mostly determined by the laser stray light and are in the order n e > 10 12 cm -3 . 52 The electron densities estimated in this work are well below 10 12 cm À3 just before the exit of the tube. In order to make better comparison with the measurements of the electron density by Thomson scattering and the estimation presented in this article, we calculated electron densities in the tube and the effluent of the plasma jet operating with gas flow of 1000 SCCM.…”
Section: Estimations Of the Electron Density In The Streamer Channelmentioning
confidence: 59%
“…Hübner et al [77] reported that the time-resolved n e varied in the range of (0.1-2.0) × 10 13 cm −3 and the T e ranged from 0.2-1.6 eV in a 250 ns-pulsed helium plasma jet driven at 20 kHz. A strong initial n e overshoot with a maximum of 7 × 10-13 cm −3 and a mean electron energy of 0.1-3.0 eV were observed in an argon plasma jet driven by a 3.5 kV positive dc pulse with a pulse width of 500 ns and a repetition frequency of 5 kHz [78]. Using a similar setup, Park et al [84] reported that the time-averaged n e was 1 × 10 9 cm −3 and T e was (1.0-2.5) eV via a comparison of the absolute intensity of continuum emission spectrum with the theoretically calculated neutral bremsstrahlung emissivity.…”
Section: Plasma Jetmentioning
confidence: 99%
“…For further insights, the electrons in plasma jets has also been characterized using various electron diagnostic techniques, such as laser Thomson scattering [76][77][78], laser interferometry [79], Stark broadening of hydrogen atomic lines [80][81][82], and continuum radiation [84]. The line broadening method has been widely used for most electron studies in atmospheric-pressure plasmas, particularly in microwave-and radio-frequency-excited plasmas because of their high n e .…”
Section: Plasma Jetmentioning
confidence: 99%
“…The predicted LTS signal per one laser shot is small. However, accurate LTS measurements are possible with signal accumulation methods as done in many previous studies [4,5,15,16]. the Nd:YAG laser (Continuum, Surelite III, laser energy 130 mJ at λ = 532 nm) was used as the light source.…”
Section: Methodsmentioning
confidence: 99%